Global small‐angle X‐ray scattering data analysis for multilamellar vesicles: the evolution of the scattering density profile model. (4th February 2014) - Heftberger, Peter; Kollmitzer, Benjamin; Heberle, Frederick A.; Pan, Jianjun; Rappolt, Michael; Amenitsch, Heinz; Kučerka, Norbert; Katsaras, John; Pabst, Georg
<x xml:space="preserve">Abstract</x> The highly successful scattering density profile (SDP) model, used to jointly analyze small‐angle X‐ray and neutron scattering data from unilamellar vesicles, has been adapted for use with data from fully hydrated, liquid crystalline multilamellar vesicles (MLVs). Using a genetic algorithm, this new method is capable of providing high‐resolution structural information, as well as determining bilayer elastic bending fluctuations from standalone X‐ray data. Structural parameters such as bilayer thickness and area per lipid were determined for a series of saturated and unsaturated lipids, as well as binary mixtures with cholesterol. The results are in good agreement with previously reported SDP data, which used both neutron and X‐ray data. The inclusion of deuterated and non‐deuterated MLV neutron data in the analysis improved the lipid backbone information but did not improve, within experimental error, the structural data regarding bilayer thickness and area per lipid.